CRISPR/Cas9-mediated mutation on an insulin-like peptide encoding gene affects the growth of the ridgetail white prawn Exopalaemon carinicauda - Gao, Yi; Zhang, Xiaojun; Yuan, Jianbo; Zhang, Chengsong; Li, Shihao; Li, Fuhua (Frontiers in Endocrinology, 2022)
Insulin-like peptides (ILPs) play key roles in animal growth, metabolism and reproduction in vertebrates. In crustaceans, one type of ILPs, insulin-like androgenic gland hormone (IAG) had been reported to be related to the sex differentiations. However, the function of other types of ILPs is rarely reported. Here, we identified another type of ILPs in the ridgetail white prawn Exopalaemon carinicauda (EcILP), which is an ortholog of Drosophila melanogaster ILP7. Sequence characterization and expression analyses showed that EcILP is similar to vertebrate insulin/IGFs and insect ILPs in its heterodimeric structure and expression profile. Using CRISPR/Cas9 genome editing technology, we generated EcILP knockout (KO) prawns. EcILP-KO individuals have a significant higher growth-inhibitory trait and mortality than those in the normal group. In addition, knockdown of EcILP by RNA interference (RNAi) resulted in slower growth rate and higher mortality. These results indicated that EcILP was an important growth regulator in E. carinicauda.